Geographical Location Determines the Population Structure in Phyllosphere Microbial Communities of a Salt-Excreting Desert Tree - Finkel, Omri M. (American Society for Microbiology, 2011)
The leaf surfaces of Tamarix, a salt-secreting desert tree, harbor a diverse community of microbial epiphytes. This ecosystem presents a unique combination of ecological characteristics and imposes a set of extreme stress conditions. The composition of the microbial community along ecological gradients was studied from analyses of microbial richness and diversity in the phyllosphere of three Tamarix species in the Mediterranean and Dead Sea regions in Israel and in two locations in the United States. Over 200,000 sequences of the 16S V6 and 18S V9 hypervariable regions revealed a diverse community, with 788 bacterial and 64 eukaryotic genera but only one archaeal genus. Both geographic location and tree species were determinants of microbial community structures, with the former being more dominant. Tree leaves of all three species in the Mediterranean region were dominated by Halomonas and Halobacteria, whereas trees from the Dead Sea area were dominated by Actinomycetales and Bacillales. Our findings demonstrate that microbial phyllosphere communities on different Tamarix species are highly similar in the same locale, whereas trees of the same species that grow in different climatic regions host distinct microbial communities.